(3cJGH GdMjd hGdMQha hMaX GdeOGFf hGdOQhHs - (3GHf efcdj , eMeO Hf efcdj GdfGUQj,J (B770 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGSY Pi GdfYe hGdBdGA gPG cJGH GdMjd hGdMQhH haJM GdeOGjf hMaX GdOQhH s
(3BNQgG (B:s
(3hdcd hLg ef Pdc VQH def GdefYgI SbfGg ai eMdg hGddg JYGdi CYde s
(3fSNI NRGFfjIs
(3Ydjg JedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B112 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B8s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs